Objek Wisata Sejarah Lubang Jepang: Studi Sosial dan Ekonomi Mayarakat di Panorama Kota Bukittinggi tahun 2001-2020 - Feni Astriani; Azmi Fitrisia (Jurusan Sejarah FIS UNP, 2022)
This study discusses the policies of the Bukittinggi City Government in the field of tourism, the management of the Japanese Hole and the impact of the Japanese Hole on the Panorama community who are involved in tourism and the impact on the Government and Visitors. The purpose of this study is to explain the policies of the Bukittinggi City Government, the management of the Japanese Hole and its impact on the Panorama community, the government and visitors. This research includes historical qualitative research using historical methods in the form of interviews, literature studies, and archive studies. From the discussion, it can be seen that, firstly, the Bukittinggi City Government policy refers to the strategic plan (RESTA), both the Japanese Hole tourist attraction began to be discussed by the Bukittinggi City Tourism Office in 2001 with various developments in 2004, namely the revitalization program, the determination of cultural heritage in 2018, and the availability of facilities and changes in user fees for visitors, the third impact of the existence of the Japanese Hole tourist attraction on the Panorama Community involved as food traders, souvenir traders and tour guides as well as the impact on the government, namely the existence of PAD and tourism promotion and visitors, namely getting historical insight obtained from the tour. guide and hands-on experience seeing the Japanese Hole. Keywords: Impact, Japan Hole, Socio-Economic